Chemical Pulps for Wrapping Papers from a Mixture of Broad-leaved Woods - Guha, S. R. D.; Singh, Man Mohan; Saxena, V. B. (Indian Forester, 1961)
Laboratory experiments on the pulping of a mixture of woods of broad-leaved trees frnm Madhya Pradesh for the manufacture of wrapping paper by the sulphate process are described. Encouraging results were obtained.